2012
DOI: 10.1002/imhj.21376
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Responsiveness, Intrusiveness, and Negativity During Play with Infants: Contextual Associations and Infant Cognitive Status in A Low‐Income Sample

Abstract: Maternal parenting behaviors during a mother-infant play interaction were examined in a sample of 160 low-income mothers and their 15-month-old infants. Maternal responsive/didactic, intrusive, and negative behaviors were coded from videotapes and examined in relation to mothers' age, marital status, stressful life events, and depressive symptoms, and infants' cognitive scores at 15 and 25 months. Younger maternal age and increases in stressful life events were associated with increases in mothers' negative be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 101 publications
(123 reference statements)
4
54
0
Order By: Relevance
“…Additionally, multiple regression models tend to explain more of the variance in cognitive outcomes when compared to a cumulative index approach (24,28,37). Several adversities emerged as significant predictors of child cognitive ability, after accounting for other exposures, including those associated with low socioeconomic status (22,28,29), neighborhood safety (28), and maternal depression (29,39). Among studies of executive function, one study showed that family chaos and instability, but not poverty, was associated with diminished inhibitory control among preschool-aged children (38).…”
Section: Salient Adverse Experiences and Cognitive Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, multiple regression models tend to explain more of the variance in cognitive outcomes when compared to a cumulative index approach (24,28,37). Several adversities emerged as significant predictors of child cognitive ability, after accounting for other exposures, including those associated with low socioeconomic status (22,28,29), neighborhood safety (28), and maternal depression (29,39). Among studies of executive function, one study showed that family chaos and instability, but not poverty, was associated with diminished inhibitory control among preschool-aged children (38).…”
Section: Salient Adverse Experiences and Cognitive Developmentmentioning
confidence: 99%
“…McFadden and Tamis-Lemoda explored multiple parenting behaviors under conditions of socioeconomic disadvantage, including poverty, stressful life events, and maternal depression, and found that nonresponsive parenting mediated the effects of maternal depression on the cognitive outcomes of 2-y-old infants while there was no effect of intrusive or negative parenting (39). Another study showed that the quality of the home environment (i.e., the extent to which the environment is stimulating, safe, and responsive) also mediated the relationship between maternal substance use and cognitive competence (28).…”
Section: Underlying Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitive parents are emotionally available, engaged and responsive to children’s signals and needs, cognitively stimulating, warm, and not harsh or hostile (McFadden & Tamis-LeMonda, 2013; Whiteside-Mansell, Bradley, Owen, Randolph, & Cauce, 2003). Insensitivity can be marked by emotional detachment from the child; negativity toward the child; and/or intrusive, overly directive behavior that undermines the child’s autonomy.…”
Section: Parental Sensitivity In Hispanic Parentsmentioning
confidence: 99%
“…Insensitivity can be marked by emotional detachment from the child; negativity toward the child; and/or intrusive, overly directive behavior that undermines the child’s autonomy. Given the risks for academic difficulties for children of low socioeconomic and ethnic minority status, sensitive parenting may be a particularly important protective factor (McFadden & Tamis-LeMonda, 2013). …”
Section: Parental Sensitivity In Hispanic Parentsmentioning
confidence: 99%